Analisis Kecerdasan Emosional Pada Mahasiswa Psikologi Islam Institut Agama Islam Negeri Kediri - J.A, abdatul (FKIP Universitas Muhammadiyah Sukabumi, 2023)
The study is intended to analyze and describe the emotional intelligence of III semester psych class students. The methods in this study use descriptive methods with a qualitative approach. The subject of this study is 29 students of III semester psychology. The data collection involves observation, interviews, distribution of angkets, and documentation. Results from the data analysis suggest that in this early adult phase there are some learners who still have not been able to recognize their own emotional condition. still remarkably stable in his emotional control. The percentage of its stability in the preferred response in the commission of his teacher was 86.2% no and 138% said yes. Her emotional intelligence has not been able to control behaving or behaving according to certain conditions. Because we need to know that the task is one of his duties from a student.